Talking Back to OCD : the Program That Helps Kids and Teens Say. - March, John S. (Guilford Publications, 2006)
Fourteen-year-old Eric is plagued by thoughts that germs on his hands could be making his family sick. Kelly, age 8, feels distressed if she can't count her pencils in multiples of four. No one wants to get rid of OCD more than they do--that's why Talking Back to OCD puts the power to beat obsessions and compulsions in their hands. This uniquely designed volume is really two books in one. The first portion of each chapter teaches children and adolescents skills they can use to take charge of the illness. Instructions that follow show their parents how to provide encouragement and support. Base.